2008
DOI: 10.1007/s10815-008-9204-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural IVF cycles may be desirable for women with repeated failures by stimulated IVF cycles

Abstract: Mature oocyte retrieval followed by natural rather than stimulated in vitro fertilization might be a potential treatment for patients of advanced age when stimulated in vitro fertilization has been repeatedly unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Up to December 31, 2012, three healthy tWE lab babies have been born vaginally. This proof-of-principle study [10], as called by the investigators, suggests that infertility care may now be ''universally accessible.'' The authors showed that the IVF methodology can be significantly simplified and can result in successful outcomes at levels that compare favorably to those obtained in high-resource programs.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Up to December 31, 2012, three healthy tWE lab babies have been born vaginally. This proof-of-principle study [10], as called by the investigators, suggests that infertility care may now be ''universally accessible.'' The authors showed that the IVF methodology can be significantly simplified and can result in successful outcomes at levels that compare favorably to those obtained in high-resource programs.…”
Section: Discussionmentioning
confidence: 94%
“…Routine IVF (IVF), is slowly being challenged by simpler and more cost-effective methodologies. These include -Natural cycle IVF (nIVF) [10]. -Minimal stimulation IVF (msIVF) [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increasing awareness of side effects of ovarian stimulation and better understanding of ovarian physiology in relation to ovarian follicular growth and maturation, IVF in natural cycles has gained great attention and interest for both normal responder and poor responder patients [2][3][4][5][6] because natural cycle offers a more physiological, less drug-oriented, lower risk and more patient-friendly approach. However, the efficacy of natural IVF is hampered by the high incidence of oocyte retrieval failure (16.7-71.4%) and the relatively low pregnancy rate per embryo transfer (ET) cycle (0-23.5%) [2,4,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%